The Branch Information Infrastructure as a Part of the Digital Economy (on the Example of a Medicine) - E. D. Dreytser (Informaciâ i Innovacii, 2018)
The article deals with the development of information infrastructure of a particular sector of the economy on the example of medicine. The branch information infrastructure is studied in the context of the program ”Digital economy of the Russian Federation”. Traditional and new elements of the industry information infrastructure, changes in the traditional boundaries of the information market are identified. As the basis of the industry information infrastructure presented institutions engaged in the production and dissemination of industry information, primarily medical libraries. The most important condition for the effectiveness of the information infrastructure of the industry are the information culture of the organization and the information culture of the specialist. The role of information infrastructure of the industry as a factor of eciency of innovative activity of the industry is considered. Shows the importance of industry analysts in the determination of priority areas of research and knowledge management. The question of perspective directions of development of information infrastructure of medicine in structure of digital economy is raised.